Antioxidant, Antidiabetic and Antiproliferative Activities of Juice Extract and Residue Powder from Karanda (Carissa carandas L.) - Srithongkerd, Monruthai; Owatworakit, Amorn; Siriwong, Nongnuch (Journal of Food Health and Bioenvironmental Science, 2023)
Karanda (Carissa carandas L.) fruit has been extensively studied for various applications and used in making a variety of food and nonfood products due to the phytochemical components. In this study, the phenolic content, antioxidant activity, anti-diabetes and antiproliferative activities of the freeze-dried crude karanda juice powder (KJP) and residue powder (KRP) were investigated. The findings revealed a different yield: KJP obtained 7.76 g/100g and KRP obtained 9.89 g/100g (p≤0.05). In addition, the KRP had less moisture and water activity (aw) than the KJP, which may be associated with the sugar residue content. The KJP revealed that the total phenolic and anthocyanin content were 58.02 mg GAE/g and 0.17 mg/g, respectively. Furthermore, antioxidation activity using the DPPH and FRAP assays demonstrated 38.86 mg GAE/g and 9.08 µmol FeSO4/g, respectively. In terms of anti-diabetes activity, the crude extract of KJP inhibited α-amylase activity (98.70%) and α-glucosidase (50.86%), whereas KRP inhibited α-amylase activity (50.34%) and α-glucosidase (18.30%) when compared to acarbose. The KRP and KJP were both non-cytotoxic and inhibited the growth of human colorectal adenocarcinoma (Caco-2) cells and human liver hepatocellular carcinoma (HepG2), with IC50 values of 97.26 µg/mL and 87.06 µg/mL, respectively. Both the KJP and the KRP freeze-dried showed promise as dietary supplements or functional foods for diabetes and cancer prevention.